Narrativas sobre las dinámicas y acompañamiento familiar de un grupo de padres con hijos que presentan bajo rendimiento académico en una escuela rural de la Palma Cundinamarca (2022)
The present work was carried out with the objective of analyzing the narratives about the dynamics and family support of a group of parents with children who present low academic performance in a rural public institution in La Palma Cundinamarca. For its study, the qualitative methodology was used, the design of the narratives and the instrument used was the in-depth interview that was carried out with three parents in order to collect information regarding family dynamics, accompaniment strategies and performance meanings. academic. Regarding the results obtained, it was found that there are difficulties in the academic accompaniment carried out by the parents due to low schooling, little availability of time and organization, the parents do their accompaniment within their possibilities and as a main strategy they delegate to the fraternal subsystem to study support.